2022
DOI: 10.1038/s41467-022-28086-1
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor 2a agonists target mouse CD11c+T-bet+ B cells in infection and autoimmunity

Abstract: CD11c+T-bet+ B cells are recognized as an important component of humoral immunity and autoimmunity. These cells can be distinguished from other B cells by their higher expression of the adenosine receptor 2a. Here we address whether A2A receptor activation can affect CD11c+T-bet+ B cells. We show that administration of the A2A receptor agonist CGS-21680 depletes established CD11c+T-bet+ B cells in ehrlichial-infected mice, in a B cell-intrinsic manner. Agonist treatment similarly depletes CD11c+T-bet+ B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 87 publications
(131 reference statements)
1
14
0
Order By: Relevance
“…To further aid in studies of ABC development we also attempted to define conditions to induce ABCs in vitro (Figure 2F). In our hands we found that IL21 was critical for driving the development of a CD11c + CD21cells in vitro after stimulation with anti-CD40 (Figure 2G-H), consistent with previous reports about the essential role of IL21 in ABC development (20,(31)(32)(33). Based on our analysis of tonsil single cell dataset we further found that ABCs expressed many genes in the TGFβ signalling pathway (Figure S2E-F).…”
Section: Murine Abcs Can Be Generated In Vitro and After Sporozoite I...supporting
confidence: 92%
See 3 more Smart Citations
“…To further aid in studies of ABC development we also attempted to define conditions to induce ABCs in vitro (Figure 2F). In our hands we found that IL21 was critical for driving the development of a CD11c + CD21cells in vitro after stimulation with anti-CD40 (Figure 2G-H), consistent with previous reports about the essential role of IL21 in ABC development (20,(31)(32)(33). Based on our analysis of tonsil single cell dataset we further found that ABCs expressed many genes in the TGFβ signalling pathway (Figure S2E-F).…”
Section: Murine Abcs Can Be Generated In Vitro and After Sporozoite I...supporting
confidence: 92%
“…Cells in this ABC cluster also had the highest surface expression of FCRL4, CD11c and CD19 by CITE-seq analysis (Figure 1D). Data has been conflicting on whether ABC formation is dependent on the GC (20,26), therefore we performed VDJ analysis on identified clusters and we found ABCs were not notably different from cMBCs with respect to their antibody isotype usage (Figure S1C). Moreover, they had only marginally lower frequencies of somatic hypermutation (SHM) compared to cMBCs and GC B cells (Figure S1D), though SHM inversely correlated with the strength of expression of ABC genes (Figure S1E).…”
Section: Single Cell Rna-seq Of Human Tonsils Identifies Tfs Associat...mentioning
confidence: 95%
See 2 more Smart Citations
“…Such investigations may lead to more targeted therapies for modulating B‐cell dysfunction. For example, therapeutic inhibition of adenosine receptor 2a on CD11c + /T‐bet + MBCs 159 is potentially a means of decreasing pathogenic B‐cell responses without impairing global B‐cell function. Future investigations of the gut microbiota and/or SCFAs in studies of MS pathogenesis should include analyses of the relationship with EBV reactivation and activation of circulating MBCs, particularly MZ B cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%